The effects of psychosocial factors in physical activity promotion among overweight and obese adolescent in Yunnan Province, China using youth physical activity promotion model - Mingxue, Han (2025)
Adolescent obesity is a growing public health issue in China, with insufficient physical activity (PA) as a major contributor. Psychosocial factors play a crucial role in shaping children's PA behaviors, but research focusing on overweight and obese adolescents in this region is limited. This study employs the Youth Physical Activity Promotion Model (YPAP) to explore the influence of psychosocial factors on PA among overweight and obese adolescent in China. An intervention program combining family and school-based PA strategies was designed to assess its effect on PA levels in adolescent in Zhaotong, Yunnan. The study was conducted in two phases. Phase 1 was a cross-sectional study involving 1,500 adolescents aged 12 to 15 who completed several questionnaires on PA and psychosocial factors. Structural equation modelling was used to analyse the relationships between the variables. The final model fit the data well (χ²/df = 2.22, CFI = 0.98, GFI = 0.95, RMSEA = 0.03, SRMR = 0.07, NFI = 0.96, TLI = 0.98). The results revealed significant positive relationships between family influence (FI), peer influence (PI), perceived competence (PC), enjoyment, self-efficacy, and PA levels （p<0.05). However, the path coefficient from FI to PC was non-significant (β = 0.019, p > 0.05), and mediation analysis showed that the pathway from FI to PA through PC was also non-significant (effect = 0.002, p = 0.566). Additionally, psychosocial factors in the YPAP model displayed variations across different BMI and grade-level groups. Phase 2 involved a randomized controlled trial with 96 participants, who were randomly assigned to an intervention or a control group. The intervention lasted eight weeks, with three sessions per week. The interaction effects were significant for FI, PI, enjoyment, self-efficacy, and PA (p< 0.05), with the intervention group showing significantly higher scores than the control group. However, the interaction effect on PC was not significant (p = 0.077). This study highlights significant associations between psychosocial factors and PA among overweight and obese adolescent in China. Self-efficacy, FI, PI, and enjoyment are crucial factors in promoting PA. The YPAP-based intervention is effective in increasing PA levels. Future research should explore mediating or moderating variables and adjust intervention strategies based on BMI and grade-level differences to enhance effectiveness